Revealing the core suppression effects of various Di (2-ethylhexyl) phthalate exposure on early meiosis progression in postnatal male mice via single-cell RNA sequencing - Han, Baoquan; Hua, Lei; Yu, Shuai; Ge, Wei; Huang, Cong; Tian, Yu; Li, Chunxiao; Yan, Jiamao; Qiao, Tian; Guo, Jiachen; Lu, Dongliang; Wang, Bin; et al. (Ecotoxicology and environmental safety, 2025)
The male reproductive system has been the subject of considerable attention in recent years due to the adverse effects of Di (2-ethylhexyl) phthalate (DEHP). Although previous research has suggested that DEHP exposure hinders the early meiotic progression of male germ cells, the underlying mechanisms are still not well understood. The transcriptomic changes in testicular cells of postnatal male rodents following DEHP exposure were meticulously analyzed using 10X Genomics single-cell RNA sequencing in this study. For downstream analysis, we acquired 42,000 cells and generated 3172,754,990 reads. DEHP exposure at concentrations of 40 μg/kg/day (DEHP40) and 80 μg/kg/day (DEHP80) substantially decreased the proportion of pachytene and diplotene spermatocytes, indicating a shared inhibitory effect on early meiosis, as demonstrated by our findings. In addition, DEHP exposure disrupted the cellular communication between Sertoli cells and germ cells, which had a significant impact on the p38-MAPK signaling pathway. The expression of key ligand genes Tgfb1 and Tgfb3 in Sertoli cells was significantly reduced. DEHP exposure resulted in a substantial decrease in the expression of the Trp53 gene, which in turn down-regulated three critical downstream genes (Stmn1, Tubb5, and Ccnb1) that are implicated in spindle organization from a mechanistic perspective. This study offers the first comprehensive evidence that DEHP inhibits early meiotic progression in male germ cells through the Trp53-mediated p38-MAPK pathway, providing crucial insights into the molecular mechanisms underlying DEHP-induced male reproductive toxicity. Our results emphasize the enduring negative effects of DEHP exposure on male fertility, which have substantial ramifications for the comprehension and mitigation of the influence of environmental estrogens on reproductive health. [Display omitted] •DEHP Exposure Inhibits Early Meiosis: Di (2-ethylhexyl) phthalate (DEHP) exposure significantly reduces the proportion of pachytene and diplotene spermatocytes, indicating a shared inhibitory effect on early meiosis in postnatal male mice.•Disruption of Cellular Communication: DEHP exposure disrupts the communication between Sertoli cells and germ cells, particularly affecting the p38-MAPK signaling pathway. Key ligand genes Tgfb1 and Tgfb3 in Sertoli cells are significantly down-regulated.•Trp53-Mediated Pathway: DEHP exposure leads to a substantial decrease in the expression of the Trp53 gene, which in turn down-regulates critical downstream genes (Stmn1, Tubb5, and Ccnb1) involved in spindle organization.•p38-MAPK Pathway: The study highlights the essential role of the Trp53-mediated p38-MAPK pathway in DEHP’s inhibitory effect on early meiosis progression, offering a potential target for mitigating reproductive toxicity.